2018
DOI: 10.1111/ajad.12762
|View full text |Cite
|
Sign up to set email alerts
|

Lost in virtual gaming worlds: Grit and its prognostic value for online game addiction

Abstract: This study provides initial support for the clinical relevance of grit for online game addiction. (Am J Addict 2018;XX:1-6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
1
19
0
4
Order By: Relevance
“…The same studies also reported that IGD was predicted by negative valence (Charlton and Danforth 2010), schizotypal traits (Schimmenti et al 2017), narcissism (Kırcaburun et al 2018;Kim et al 2008), sadism (Kırcaburun et al 2018), grit (Borzikowsky and Bernhardt 2018), negative affectivity, detachment, and psychoticism (Laier et al 2018). Others reported that IGD was negatively correlated with histrionic trait (Gonzalez-Bueso et al 2018), grit (i.e., ability to be persistent in pursuit of long-term goals) (Borzikowsky and Bernhardt 2018), and oppositional and self-demeaning traits (which refer to self-defeating personality disorder patterns at DSM-II-R) (Torres-Rodríguez et al 2018). Finally, one investigated temperament and character components of personality, and reported that those with IGD had higher novelty seeking and harm avoidance scores than the healthy individuals (Lee et al 2017).…”
Section: Personality Traits Associated With Internet Gaming Disordermentioning
confidence: 92%
See 4 more Smart Citations
“…The same studies also reported that IGD was predicted by negative valence (Charlton and Danforth 2010), schizotypal traits (Schimmenti et al 2017), narcissism (Kırcaburun et al 2018;Kim et al 2008), sadism (Kırcaburun et al 2018), grit (Borzikowsky and Bernhardt 2018), negative affectivity, detachment, and psychoticism (Laier et al 2018). Others reported that IGD was negatively correlated with histrionic trait (Gonzalez-Bueso et al 2018), grit (i.e., ability to be persistent in pursuit of long-term goals) (Borzikowsky and Bernhardt 2018), and oppositional and self-demeaning traits (which refer to self-defeating personality disorder patterns at DSM-II-R) (Torres-Rodríguez et al 2018). Finally, one investigated temperament and character components of personality, and reported that those with IGD had higher novelty seeking and harm avoidance scores than the healthy individuals (Lee et al 2017).…”
Section: Personality Traits Associated With Internet Gaming Disordermentioning
confidence: 92%
“…With regard to key methodological features of studies, all studies reviewed were empirical and quantitative nature. The majority of the studies employed a cross-sectional design (Braun et al 2016;Charlton and Danforth 2010;Chiu et al 2004;Collins et al 2012;Gonzalez-Bueso et al 2018;Kim et al 2008;Kim et al 2016;Lee et al 2017;Lehenbauer-Baum and Fohringer 2015;Mehroof and Griffiths 2010;Müller et al 2014;Schimmenti et al 2017;Torres-Rodríguez et al 2018;Walther et al 2012;Wang et al 2015;Wittek et al 2016), and five studies adopted a mixed-methods design (Borzikowsky and Bernhardt 2018;Hu et al 2017;Kırcaburun et al 2018;Laier et al 2018;Li et al 2016). Excluding three studies that combined both self-report questionnaires and clinical interviews (Gonzalez-Bueso et al 2018;Müller et al 2014;Torres-Rodríguez et al 2018), the remaining 18 studies used self-report questionnaires to collect data.…”
Section: Methodological Features Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations